Heparan Sulfate Is an Attachment Factor for Foamy Virus Entry - Plochmann, Kathrin (American Society for Microbiology, 2012)
The cellular receptor of foamy viruses (FVs) is unknown. The broad spectrum of permissive cells suggests that the cellular receptor is a molecular structure with almost ubiquitous prevalence. Here, we investigated the ability of heparan sulfate (HS), a glycosaminoglycan (GAG) present on the extracellular matrix of many cells, to bind FV particles and to permit prototype FV (PFV) and feline FV (FFV) entry. Permissivity of different cell lines for FV entry correlated with the amount of heparan sulfate present on the cell surface. The resulting 50% cell culture infectious doses (CCID(50)s) were distributed over a range of 4 logs, which means that the most susceptible cell line tested (HT1080) was more than 10,000 times more susceptible for PFV infection than the least susceptible cell line (CRL-2242). HS surface expression varied over a range of 2 logs. HS expression and FV susceptibility were positively correlated (P < 0.001). Enzymatic digestion of heparan sulfate on HT1080 cells diminished permissivity for PFV entry by a factor of at least 500. Using fast protein liquid chromatography (FPLC), we demonstrated binding of FV vector particles to a gel filtration column packed with heparin, a molecule structurally related to heparan sulfate, allowing for the purification of infectious particles. Both PFV and FFV infection were inhibited by soluble heparin. Our results show that FVs bind to HS and that this interaction is a pivotal step for viral entry, suggesting that HS is a cellular attachment factor for FVs.